Instagram and lumbar discectomy surgery: An evaluation of patients’ perception of surgery in social media: Lumbar discectomy evaluation in Instagram - Kultur, Yigit; Karaca, Sinan; Erdem, Mehmet Nuri; Sahin, Erdem; Gasimov, Elviz; Biscevic, Mirza; Tezer, Mehmet (Journal of Surgery and Medicine, 2023)
Background/Aim: Most scoring systems in healthcare take into account the physical condition and pain status of a patient, but the impact of society on the individual is ignored. The aim of our study was to evaluate the social media posts made by patients regarding lumbar discectomy surgery. The objective was to identify and explore concerns and issues that may not be immediately evident during clinical evaluations but are significant to the patients themselves. Methods: Public posts with the hashtags #discectomy, #lumbardisectomy, and #discectomyrecovery were examined on the Instagram application. The tone of the post, return to sports (RTS), rehabilitation or physical therapy (PT), return to work (RTW), incision site (e.g., scarring, sutures, and dressing), pain, activities of daily living (ADL), and X-ray/magnetic resonance imaging (MRI) data were evaluated. The "Instagram likes ratio" was determined by dividing the total number of likes received for each post by the number of followers. Results: 272 posts were assessed, and 77.9% of them exhibited a positive tone. The topic that was most frequently discussed was ADL, which was discussed in 24.6% of the posts. Statistical analysis demonstrated a significant association between positive tone and ADL, as well as positive tone and RTS (P<0.001). A statistically significant correlation was observed between negative tone and neurological deficits, pain, and X-ray/MRI findings (P<0.001). Conclusion: Our study offers a unique perspective on the experience and satisfaction of patients who have undergone lumbar discectomy. Neurologic deficits and pain were notably significant in the negative posts. However, in general, the majority of the posts maintained a positive tone. The results could provide insights into patients’ experiences and perspectives that can potentially inform healthcare professionals in providing more comprehensive and patient-centered care.